2017
DOI: 10.1007/s10517-017-3814-y
|View full text |Cite
|
Sign up to set email alerts
|

Express Estimation of the Biological Age by the Parameters of Body Composition in Men and Women over 50 Years

Abstract: Original formulas for rapid assessment of biological age in men and women over 50 were developed using factor analysis. The proposed technique is mainly based on the parameters of the body component composition (fat, musculoskeletal, and active cell mass, and specific metabolism) obtained using bioimpedance recording widely used in modern medicine and anthropology. The proposed formulas were tested on other samples (481 examined subjects). The developed method of express estimation of biological age differs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Furthermore, these measures could be combined with other known and emerging biological correlates of aging, including molecular markers (obtained from the peripheral blood, for example 52,53 ), gene expression 8 , body composition 54 , microbiome 55 , and other imaging modalities such as x-rays 56 , CT 57 or MRI 58 . We have already demonstrated that FaceAge is correlated with genes implicated in cellular senescence, as well as with skeletal muscle index, a body composition measure already known to be prognostic of survival in cancer patients 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these measures could be combined with other known and emerging biological correlates of aging, including molecular markers (obtained from the peripheral blood, for example 52,53 ), gene expression 8 , body composition 54 , microbiome 55 , and other imaging modalities such as x-rays 56 , CT 57 or MRI 58 . We have already demonstrated that FaceAge is correlated with genes implicated in cellular senescence, as well as with skeletal muscle index, a body composition measure already known to be prognostic of survival in cancer patients 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…Body composition has been previously explored for the evaluation of BA, identifying sex‐based differences in anthropometric parameters that are linearly associated with CA (Bae et al, 2012 ; Negasheva et al, 2017 ). In contrast to these previous studies, AnthropoAge uses a nonlinear approach to link body composition patterns to mortality risk, which has been speculated to be a better surrogate of BA; this in turn may clarify the relationship of body composition with aging and age‐related outcomes beyond individual metrics such as BMI, given that these alone do not completely capture the complexity of this phenomenon (Donini et al, 2020 ; Lavie et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…With all this, it is unsurprising that body composition is often recognized as one of the main domains in which aging takes place (Kuo et al, 2020 ). However, despite the overwhelming evidence supporting the contribution of body composition and anthropometry to predict age and age‐related outcomes, their proper implementation in the development of BA estimations has been limited (Bae et al, 2012 ; Negasheva et al, 2017 ). Here, we hypothesize that the integration of sex‐based differences in multiple anthropometric measurements would result in the development of a reliable and easily implementable BA estimation that captures the body composition domain of aging.…”
Section: Introductionmentioning
confidence: 99%
“…Body composition has been previously explored for the evaluation of BA, identifying sex-based differences of anthropometric parameters that are linearly associated with CA (Kang et al, 2012; Negasheva et al, 2017). In contrast to these previous studies, AnthropoAge uses a non-linear approach to link body composition patterns to mortality risk, which has been speculated to be a better surrogate of BA; this in turn may clarify the relationship of body composition with aging and age-related outcomes beyond individual metrics such as BMI, given that these alone do not completely capture the complexity of this phenomenon (Donini et al, 2020; Lavie et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…With all this, it is unsurprising that body composition is often recognized as one of the main domains in which aging takes place (P. -L. Kuo et al, 2020). However, despite the overwhelming evidence supporting the contribution of body composition and anthropometry to predict age and age-related outcomes, their proper implementation in the development of BA estimations has been limited (Kang et al, 2012; Negasheva et al, 2017). Here, we hypothesize that the integration of sex-based differences in multiple anthropometric measurements would result in the development of a reliable and easily implementable BA estimation that captures the body composition domain of aging.…”
Section: Introductionmentioning
confidence: 99%